KARAKTERISTIK MIE KERING TERBUAT DARI TEPUNG SUKUN (Artocarpus altilis) DAN PENAMBAHAN TELUR - Utiya Listy Biyumna; Wiwik Siti Windrati; Nurud Diniyah (JURNAL AGROTEKNOLOGI, 2017)
Dry noodle is dry food product that is usually made from wheat flour with food ingredients and food additives permitted. Breadfruit is a high carbohydrate of food as much as 78.9% if the breadfruit was bundled. High carbohydrate content in breadfruit flour can be used as a substitute food in noodle, but the protein content is low, it is necessary to add foods containing high protein, such as egg. The purpose of this research was to know the best influence and formulation on physical, sensorial and chemical characteristics of dry noodles substituted by breadfruit flour and egg. Design experimental in this research was used Completely Randomized Design (CRD) arranged as factorial with two factors, first factor (A) were ratio of wheat flour and breadfruit flour which include A1 (90% of wheat flour and 10% of breadfruit flour), A2 ( 80% of wheat flour and 20% of breadfruit flour) and A3 (70% of wheat flour and 30% of breadfruit flour, while the second factor (B) was addition of egg include B1 (5% of egg), B2 (10 % of egg) and B3 (15% of egg). The best treatment was dry noodle which made from 90% of wheat flour : 10% of breadfruit flour and 15% of egg. The best characteristic of dry noodle has 11.72% protein content, moisture content 9.55%, ash content 0,58%, fat content 1.12%, carbohydrate 77.04%, lightness 62,58, elasticity 26.60 kg/s2, cooking loss 7.11%, power rehydration 151,36%; likes of color, smell, flavor, texture and overall favorite 4.3; 4.23; 4.37; 4.2; 4.4 (like-very like). Keywords: dry noodle, substitution, breadfruit flour, egg